Stenotrophomonas maltophilia virulence: a current view - Mikhailovich, Vladimir; Heydarov, Rustam; Zimenkov, Danila; Chebotar, Igor (Frontiers in Microbiology, 2024)
Stenotrophomonas maltophilia is an opportunistic pathogen intrinsically resistant to multiple and broad-spectrum antibiotics. Although the bacterium is considered a low-virulence pathogen, it can cause various severe diseases and contributes significantly to the pathogenesis of multibacterial infections. During the COVID-19 pandemic, S. maltophilia has been recognized as one of the most common causative agents of respiratory co-infections and bacteremia in critically ill COVID-19 patients. The high ability to adapt to unfavorable environments and new habitat niches, as well as the sophisticated switching of metabolic pathways, are unique mechanisms that attract the attention of clinical researchers and experts studying the fundamental basis of virulence. In this review, we have summarized the current knowledge on the molecular aspects of S. maltophilia virulence and putative virulence factors, partially touched on interspecific bacterial interactions and iron uptake systems in the context of virulence, and have not addressed antibiotic resistance.